An integrated lab-on-chip for rapid identification and simultaneous differentiation of tropical pathogens. - Jeslin J L Tan; Monica Capozzoli; Mitsuharu Sato; Wanitda Watthanaworawit; Clare L Ling; Marjorie Mauduit; Benoît Malleret; Anne-Charlotte Grüner; Rosemary Tan; François H Nosten; Georges Snounou; Laurent Rénia; et al. (Public Library of Science (PLoS), 2014)
Tropical pathogens often cause febrile illnesses in humans and are responsible for considerable morbidity and mortality. The similarities in clinical symptoms provoked by these pathogens make diagnosis difficult. Thus, early, rapid and accurate diagnosis will be crucial in patient management and in the control of these diseases. In this study, a microfluidic lab-on-chip integrating multiplex molecular amplification and DNA microarray hybridization was developed for simultaneous detection and species differentiation of 26 globally important tropical pathogens. The analytical performance of the lab-on-chip for each pathogen ranged from 102 to 103 DNA or RNA copies. Assay performance was further verified with human whole blood spiked with Plasmodium falciparum and Chikungunya virus that yielded a range of detection from 200 to 4×105 parasites, and from 250 to 4×107 PFU respectively. This lab-on-chip was subsequently assessed and evaluated using 170 retrospective patient specimens in Singapore and Thailand. The lab-on-chip had a detection sensitivity of 83.1% and a specificity of 100% for P. falciparum; a sensitivity of 91.3% and a specificity of 99.3% for P. vivax; a positive 90.0% agreement and a specificity of 100% for Chikungunya virus; and a positive 85.0% agreement and a specificity of 100% for Dengue virus serotype 3 with reference methods conducted on the samples. Results suggested the practicality of an amplification microarray-based approach in a field setting for high-throughput detection and identification of tropical pathogens.